THE ROLE OF CORPORATE ZAKAT ON OPTIMAL CAPITAL STRUCTURE POLICY: EVIDENCE FROM MALAYSIAN FIRMS - Talattov, Abrapuspa Ghani; Sanusi, Nur Azura; Kusairi, Suhal; Shaari, Abu Hassan (Journal of Islamic Monetary Economics and Finance, 2016)
In the finance literature, the relationship between capital structure and firm value has been extensively investigated, both theoretically and empirically. The main issue on corporate finance is how firms dealing with the important decision of capital structure. In this study, a model of capital structure is formulated in which corporate tax and zakat payment exist by firms into the consideration of combination of debt and equity. The theoretical model as shown by comparative statics prove the implication which is negatively relationship between leverage of the firm and the corporate zakat payment. Meanwhile, the empirical evidence reveals several implication as follows, (1) tax deduction reduces the current liability item relative to the firms that prefer equity financing, (2) the significant of zakat is consistent with the theoretical model that zakat would encourage firm to issue more equity than debt, (3) the strong significant relationship between return on assets with the leverage are the leading indicator of capital structure in all models.